Effective Communication in Character Education: A Pathway to Strengthening Nationalism of SMP Swasta Islam Terpadu Jabal Noor Student - Dalimunthe, Maulana Andinata; Ritonga, Aulia Rahma; Dalimunthe, Nisaul Fadilah; Veronica, Afryna (Talenta Publisher, 2025)
This research explores the role of effective communication in character education to enhance nationalism among students at SMP Swasta Islam Terpadu Jabal Noor. Utilizing a descriptive qualitative approach, data were collected through observations and in-depth interviews with the principal, vice principal, and homeroom teacher. The findings reveal that effective communication strategies, including lectures, group discussions, and the use of digital media, play a pivotal role in embedding nationalistic values within students. The study highlights that integrating digital tools in delivering character education makes learning more engaging and impactful for digital-native students. Despite challenges such as limited infrastructure and digital literacy, the approach effectively instills moral and civic virtues. This research emphasizes the need for innovative communication strategies in Islamic educational institutions to bridge religious values and nationalism, fostering a harmonious and unified generation prepared to navigate the complexities of modern society.